Study of Negative Symptoms among 100 Schizophrenic Patients - Bhuiyan, Anwar Parvez; Islam, Md Azizul; Islam, Md Monirul; Hasin, Atiyah (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Schizophrenia is a clinical syndrome of variable but profoundly disruptive, psychopathology that involves cognition, emotion, perception and other aspects of behavior. The expression of these manifestations varies across patients and over time, but the effect of the illness is always severe and usually long lasting. The disorder usually begins before age 25, persists throughout life, and affects persons of all social classes. Both patients and their families often suffer from poor care and social ostracism because of widespread ignorance about the disorder. Schizophrenia is equally prevalent in men and women. Objective: To find out the pattern and frequency of negative symptoms in Schizophrenic patients. Materials and Methods: This descriptive cross-sectional study was conducted from 1st June to 31st December 2014 among 100 schizophrenic patients. For demographic assessment every patient was interviewed by a semi-structured questionnaire, after taking informed consent. Scale for the Assessment of Negative Symptoms (SANS) was used to interview the Schizophrenic patient. The scale is internationally well accepted research instrument for assessing negative symptoms in Schizophrenic patient. The study was conducted in Combined Military Hospital (CMH), Dhaka, National Institute of Mental Health (NIMH), Dhaka and Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Sampling size was 100 where Schizophrenia was diagnosed by psychiatrists. Results: The age group of the patients was from 18 years to 59 years with mean age 27.3 years (SD ±11.0), most of the patients were below the age of 30 years. Eighty six (86%) out of one hundred patients were found to have negative symptom. Most of the patient were male, literate, Muslim and came from a middle class family background. Onset of the disease was mostly insidious in nature. Conclusion: Schizophrenia is a major psychiatric disorder. Both the patient and their families suffer a lot by schizophrenia and its consequences. So improving the management of negative symptoms may reduce the overall burden of schizophrenic patients and their caregivers. JAFMC Bangladesh. Vol 17, No 1 (June) 2021: 22-25